Unveiling the link: Evaluating MTHFR gene polymorphisms and colorectal cancer risk through meta-analysis - Yu-wei Wang; Ze-yi Huang; Chen-xue Jin; Xiao-hui Shen; Xiao-feng He; Chang-qing Yang (PLoS ONE, 2025)
Colorectal cancer pathogenesis is a multifactorial process, with genetic factors playing a significant role in cancer development. A review of published meta-analyses on MTHFR gene polymorphisms and colorectal cancer susceptibility showed inconsistent findings and failed to assess the reliability of statistically significant results. Case-control studies were manually searched in databases to investigate the association between MTHFR gene polymorphisms and colorectal cancer. The study assessed the strength of association for the five gene models by calculating odds ratios (ORs) and 95% confidence intervals (CIs). The study results were also analyzed for the source of heterogeneity, sensitivity, publication bias, and false-positive report probability (FPRP) test. Additionally, extensive subgroup analyses were conducted to investigate the impact of confounding factors on the associations. The study suggests that MTHFR C677T gene polymorphism reduces the risk of colorectal cancer in Asian and mixed-race populations, while increasing the risk of Colorectal cancer in the Indian ethnic group. MTHFR A1298C may play a protective role in the development of colorectal cancer. These findings provide valuable insights for the early diagnosis and prevention of Colorectal cancer. However, further studies are required to confirm the association, which may offer additional information for the early diagnosis and prevention of Colorectal cancer.